Parametric Study of Oil-Water Dispersion Separation in Horizontal Pipelines Using a Mechanistic Model - Evripidou, Nikola (My University, 2025)
Oil-water dispersed flows are common in the petroleum industry. While gravity-driven separation enables phase segregation, persistent settling layers reduce separation efficiency. This study conducts a parametric investigation using a mechanistic model to identify factors contributing to settling layer persistence. Droplet size, dispersed-phase fraction, and pipe diameter are varied to evaluate their effects. Results, presented as separation regime maps, identify the dominant separation mechanism under different conditions. Smaller droplets, higher dispersed-phase fractions, and larger pipe diameters promote settling layer persistence. A near-linear relationship is also found between droplet size and critical pipe diameter at which a persistent settling layer is observed.